PEMAKNAAN PRINSIP KEPENTINGAN DALAM HUKUM ASURANSI DI INDONESIA - Wulansari, Retno (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2017)
The insurable interest principle in Indonesia’s insurance system is governed by Article 250 and Article 286 the Code of Bussiness Law (KUHD). In the formulation of the Article is not mentioned about when the element of interest should exist as well as the definition of interest in the insurance agreement. This research intends to find out how the meaning of the insurable interest in the insurance system in Indonesia. The method used in this research is normative juridical, which examines the rules in the Law, principles, doctrines and other legal documents. This research result conclusion that the element of interest must exist or can be proven by the insured when the event that causing losses occurred The insured must be able to prove the existence of an economic attachment to the object or event that is contracted in the insurance agreement. The limitation of the element of interest is something that can be judged by money and which can not be judged by money for example, life, family relations, children, wife, husband and others. As for the author's suggestion is the government complement the rules in the field of insurance, especially on the insurable interest. The arrangement can explain the limits of understanding and the time when the element of interest must exist in the insurance agreement.